A new history of Malaysia: a special insight 173 into the root problems in the process of building a nation, 1945 - 2005 - Nordi Achie; Siti Aidah Lukin @ Lokin (Penerbit UMS, 2009)
This article discusses the efforts involved in building a nation from the historical perspective. It also explains political phenomena and social issues, which a based on assumptions and racial prejudice. The negative effects of racial economics and economic development as well as educational differences during the time of British colonization are also discussed. Despite facing challenges in the building of a nation, the government has designed and executed plans through various policies applied to the economy, education, the national language and culture in order to realize the formation of the Malaysian nation. It is crucial for all members of the nation, regardless of their background, to be aware of the importance of nation building so that it will become a success.